Pandas in Action - Paskhaver, Boris (Manning Publications, 2021)
"Take the next steps in your data science career! This friendly and hands-on guide shows you how to start mastering Pandas with skills you already know from spreadsheet software. Pandas has rapidly become one of Python's most popular data analysis libraries. In Pandas in Action, a friendly and example-rich introduction, author Boris Paskhaver shows you how to master this versatile tool and take the next steps in your data science career. You'll learn how easy Pandas makes it to efficiently sort, analyze, filter and munge almost any type of data. You'll learn to automate repetitive operations and gain deeper insights into your data that would be impractical--or impossible--in Excel. Each chapter is a self-contained tutorial. Realistic downloadable datasets help you learn from the kind of messy data you'll find in the real world."
Includes index. - Online resource; title from digital title page (viewed on November 09, 2021)
Keywords: Application program interfaces (Computer software); Interfaces de programmation d'applications; APIs (interfaces)